Sliding Mode Observer and Backstepping Control for a Quadrotor Unmanned Aerial Vehicles - Madani, T.; Benallegue, A. (2007 American Control Conference, 2007)
In this paper, we propose a new approach of the backstepping control running parallel with a sliding mode observer for a quadrotor unmanned aerial vehicle. The sliding mode observer works as an observer of the quadrotor velocities and estimator of the external disturbances such as wind and parameter uncertainties. The controller objective is to achieve good tracking of desired (x,y,z) absolute positions and yaw angle while keeping the stability of the pitch and roll angles, in spite of the presence of bounded external disturbances. For this reason, the observer-controller is proposed to estimate the effect of external perturbations in order to compensate them. The design methodology is based on Lyapunov stability. Simulation results show the good performances and the robustness of the proposed observer-controller.